(untitled) (Foro de Educacion, 2024)
This essay proposes re-imagining fundamental elements of the agroecological approach as contributions to formal education, particularly in post-colonial societies, to promote the installation of educational and pedagogical practices of epistemic justice in the framework of the current global Agenda for Sustainable Development and Climate Change Education. As contextualisation, we present a general discussion on the conditions of injustice within the historical development of formal education as a reproductive device of the modern Eurocentric project, considering its implications for the shared goal of achieving educational equity. We analyse two interpretations of this goal, one from a compensatory viewpoint and the other from a perspective of epistemic justice and discuss the consequences of both interpretations for thinking about educational systems, as well as for achieving justice for the students who participate in them. Considering the connections between the latter perspective and the global agreements on sustainability framed in the 2030 Agenda for Sustainable Development, we explore the theoretical, epistemological and methodological contributions of agroecology, identifying some elements of its transdisciplinary and intercultural approach, which could be operationalised by educational communities to redefine the usual relationships between educational institutions and students’ communities, as a strategy to move towards a way of formal education that promotes epistemic justice.